Template-free formation of uniform urchin-like α-FeOOH hollow spheres with superior capability for water treatment - Wang, Bao (2012)
Uniform urchin-like α-FeOOH hollow spheres assembled from nanoneedles have been synthesized via a facile and green one-pot method. By simply adjusting the amount of glycerol in the reaction system, hierarchical urchin-like α-FeOOH solid spheres or hollow spheres can be obtained. When evaluated for the potential use in water treatment, it is found that the as-obtained uniform urchin-like α-FeOOH hollow spheres exhibit excellent capability for removing both organic dye and heavy metal ions in waste water.